Analisis Strategi Pengelolaan Konten Akun Instagram @Pemkotbogor oleh Dinas Komunikasi dan Informatika Kota Bogor - Hikami Saski, Tarisha; David Rizar Nugroho (Jurnal Ilmu Komunikasi, 2025)
The purpose of this study is to understand the communication strategy for managing the Instagram account @pemkotbogor, which is managed by the Bogor City Communication and Information Agency. The method used is descriptive qualitative with in-depth interviews, observation, and documentation techniques. The results of the study show that content management is carried out systematically through the Share, Optimize, Manage, and Engage strategies. These strategies include weekly content planning, utilization of trending issues, a casual yet professional style of language, and audience engagement through direct interaction. Content evaluation and adjustment are carried out regularly to ensure that the communication strategy runs smoothly. As a result, the @pemkotbogor Instagram account has become an effective medium for building a positive image and communicating between the government and the community.